Bodies and souls, or spirited bodies? - Murphy, Nancey C. (Current issues in theology, 2006)
Are humans composed of a body and a nonmaterial mind or soul, or are we purely physical beings? Opinion is sharply divided over this issue. In this clear and concise book, Nancey Murphy argues for a physicalist account, but one that does not diminish traditional views of humans as rational, moral, and capable of relating to God. This position is motivated not only by developments in science and philosophy, but also by biblical studies and Christian theology. The reader is invited to appreciate the ways in which organisms are more than the sum of their parts. That higher human capacities such as morality, free will, and religious awareness emerge from our neurobiological complexity and develop through our relation to others, to our cultural inheritance, and, most importantly, to God. Murphy addresses the questions of human uniqueness, religious experience, and personal identity before and after bodily resurrection.